1994
DOI: 10.1007/bf00203300
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-volume-temperature behavior of ?-Fe2SiO4 (spinel) based on static compression measurements at 400� C

Abstract: Abstract. Thirteen energy-dispersive x-ray diffraction spectra for y-Fe2SiO 4 (spinel) collected in situ at 400 ~ C and pressures to 24 GPa constitute the basis for an elevated-temperature static compression isotherm for this important high-pressure phase. A Murnaghan regression of these molar volume measurements yields 177.3 (+ 17.4) GPa and 5.4(+ 2.5) for the 400 ~ C, room pressure values of the isothermal bulk modulus (Kpo) and its first pres-K' sure derivative (po), respectively. When compared to the room-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…However, an isochoric sample chamber is not an isochoric sample. It has been reported that regular resistive heating at high pressure is not isochoric [23][24][25], but partially isochoric [5], or intermediate between isochoric and isobaric [26]. Precisely speaking, for a DAC, the pressure change during a non-isochoric heating is not exactly the thermal pressure.…”
Section: The Thermal Pressure Is the Pressure Change In An Isochoric ...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, an isochoric sample chamber is not an isochoric sample. It has been reported that regular resistive heating at high pressure is not isochoric [23][24][25], but partially isochoric [5], or intermediate between isochoric and isobaric [26]. Precisely speaking, for a DAC, the pressure change during a non-isochoric heating is not exactly the thermal pressure.…”
Section: The Thermal Pressure Is the Pressure Change In An Isochoric ...mentioning
confidence: 99%
“…Thermal pressure was suggested to measure the pressure change along the isochoric contour [23,27,28], but constructing an isochoric contour is a challenge.…”
Section: The Thermal Pressure Is the Pressure Change In An Isochoric ...mentioning
confidence: 99%
“…The room temperature data anchor the high P, T equation of state. Combining our data sets with those of Suzuki et al [1979], Liu et al [2008] and Plymate and Stout [1994] we calculated a best fit high temperature equation of state using a Mie‐Grüneisen‐Debye formalism [ Dorogokupets and Dewaele , 2007]. The thermal parameters of the Grüneisen parameter γ and q are also strongly correlated, and due to the narrow pressure range of the data, the q parameter is not well constrained.…”
Section: Resultsmentioning
confidence: 99%
“…Ringwoodite (Mg,Fe) 2 SiO 4 is the spinel‐structured polymorph of olivine and likely the predominant mineral in the deep part of the transition zone [ Hirose , 2006]. While many measurements exist for the high pressure, high temperature equation of state at transition zone conditions at and close to the Mg end‐member, only a small suite of measurements exist for Fe‐ringwoodite [e.g., Mao et al , 1969; Suzuki et al , 1979; Hazen , 1993; Plymate and Stout , 1994; Nishihara et al , 2004; Liu et al , 2008] and none of these are at the pressures and temperatures of the transition zone. Significant uncertainties are introduced by extrapolating these results to relevant high pressures and temperatures, and therefore the effect of iron on the density and bulk modulus of ringwoodite is not well‐constrained at the conditions of the transition zone.…”
Section: Introductionmentioning
confidence: 99%